1985
DOI: 10.1007/bf00261578
|View full text |Cite
|
Sign up to set email alerts
|

Urinary modified nucleosides as tumor markers in cancer of the urinary organs or female genital tract

Abstract: Using a sensitive and specific method involving high-performance liquid chromatography, urinary levels of four modified nucleosides--pseudouridine (psi), 1-methylinosine (m1I), 1-methyladenosine (m1A), and 1-methylguanosine (m1G)--were investigated before and after treatment in 31 patients with cancer of the urinary organs or the female genital tract. Before treatment m1I was the most frequently elevated nucleoside (77%). Pretreatment urinary levels of psi, m1I, and m1A in patients with stage 2-4 cancer of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…It is observed that the results are similar to the situation by using 13 urinary nucleosides. These results are in agreement with the suggestions of several previous studies [9,17,24,25] although the previous samples were from German. On the other hand, attention should be paid to the alterations of the modified nucleosides under various catabolic conditions, e.g., infections, malnutrition, cardiac cachexia, and endocrine abnormalities.…”
Section: Resultssupporting
confidence: 96%
“…It is observed that the results are similar to the situation by using 13 urinary nucleosides. These results are in agreement with the suggestions of several previous studies [9,17,24,25] although the previous samples were from German. On the other hand, attention should be paid to the alterations of the modified nucleosides under various catabolic conditions, e.g., infections, malnutrition, cardiac cachexia, and endocrine abnormalities.…”
Section: Resultssupporting
confidence: 96%
“…Levels of ⌿, m 1 I, m 1 A, and m 1 G were determined before and after treatment in 31 patients with cancer of the urinary organs or the female genital tract (Koshida et al, 1985 4 C, and ⌿ were measured in the urine of 7 patients with ovarian cancer (Oerlemans & Lange, 1986). The patients were divided into three groups: benign, borderline, and malignant-based on histological criteria.…”
Section: Ovarian Cancer and Cancer Of The Female Genital Tract And Umentioning
confidence: 99%
“…cleosides with carcinogenesis [1,2] and proposed them as potential tumor markers [1,[3][4][5][6][7][8][9][10][11][12][13][14][15]. RNA contains modified nucleosides synthesized Although a capillary electrophoretic method depost-transcriptionally by modification enzymes.…”
Section: Introductionmentioning
confidence: 99%